Synthesis, characterization, and crystal structures of molybdenum complexes of unsymmetrical electron-poor dithiolene ligands. (25th September 2016) - Mohapatra, Swagat K.; Zhang, Yadong; Sandhu, Bhupinder; Fonari, Marina S.; Timofeeva, Tatiana V.; Marder, Seth R.; Barlow, Stephen
Graphical abstract: The reaction of MoS9 2− with alkynes CF3 CCCO2 Me and CF3 CCCOCF3 gives dianions of the corresponding tris(dithiolene) complexes, which can be oxidized to their neutral analogues using NOPF6 . The complexes have been characterized in various oxidation states by crystallography, electrochemistry, and UV–Vis-spectroscopy, and compared to Mo(S2 C2 (CF3 )2 )2 n and Mo(S2 C2 (CO2 Me)2 )2 n . Abstract: Mo(S2 C2 (CF3 )2 )3, 1a, has proven a useful p-dopant in organic electronics. To develop more soluble p-dopants, MoS9 2− was treated with alkynes CF3 CCCO2 Me and CF3 CCCOCF3 to give the dianions of the corresponding tris(dithiolene) complexes, 1b 2− and1c 2−, respectively, which were then oxidized to neutral molybdenum tris[1-(methoxycarbonyl)-2-(trifluoromethyl)-ethane-1, 2-dithiolene], 1b, and molybdenum tris[1-(trifluoroethanoyl)-2-(trifluoromethyl)ethane-1, 2-dithiolene], 1c, using NO + PF6 − . The crystal structures of (NEt4 + )2 1b 2−, (NEt4 + )2 1c 2−, and neutral1c have been determined. In all three cases, the metal coordination is approximately trigonal prismatic and the major isomer is cis (approximately C 3 v ). The structure of1b 2− is distorted by a twist towards pseudo-octahedral coordination similar to that seen in structures of1a 2− and Mo(S2 C2 (CO2 Me)2 )3 2−, 1d 2−, salts, and that of1c exhibits marked folds between the planes formed by the ligand atoms and those formed by the Mo and coordinated S atoms, similar to those seen in the structure of1a . On the other hand, the metal dithiolene core of1c 2− is essentially undistorted from C 3 v symmetry. The oxidant strength of the neutral molecules increases in the order1d  < 1b  < 1a  < 1c, with the potentials ranging from −0.02 to +0.39 V versus the ferrocenium/ferrocene couple.